Kajian Literatur: Kemampuan Literasi Sains dalam Pembelajaran IPA - Sakinah Zubair; Nurfitra Yanto (Universitas Negeri Makassar, 2023)
The science literacy ability of students in Indonesia is still far below the international average score. Several things that can cause this include the applicable education system, choice of models, approaches, methods, strategies, and learning methonds, choice of learning resources, student learning styles and learning infrastructure. The research method used is a literature study that examines students science literacy skills in science learning. A total of 16 articles with the theme of science literacy were collected, analyzed, and cocluded to obtain recommendations about students science literacy skills in science learning. The results of the literature review obtained several things, namely: (1) the literacy ability of students is still relatively low and one of the causes is the low science literacy ability of science educators. (2) learning models that can improve students’ science literacy skills are applying appropriate learning models including problem based learning, inquiry, ethnoscience, RQA, Discovery Model Assisted By PhET Simulation. (3) types of teaching materials that can improve students science literacy skills are guided inquiry-based teaching materials, STEM-based teaching materials, and interactive multimedia in a blended learning manner.